2016
DOI: 10.17533/udea.iee.v34n1a10
|View full text |Cite
|
Sign up to set email alerts
|

Body and Corporality in adolescents and young adults with spinal cord injury

Abstract: Objective. To describe the meaning given by adolescents and young adults to the changes in their bodies and corporality after a spinal cord injury. Methods. Qualitative study based on symbolic interactionism in which 12 adolescents and young adults, who had suffered spinal cord injury 6 months or more before, participated. The information was recollected through a series of in-depth interviews and field journals. The guidelines proposed by Corbin and Strauss were followed for the process of codification and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…It is reported that, according to this model, it is the duty of the nurse to promote the adaptive responses of the individual to changes in physiological needs, selfconcept and interdependent relationships during health and illness. 12,14,19 It was observed that the repercussions of the spinal cord injury affect the individual, the family and society, so that their coping leads the family to organize to better understand the individual and to learn to live with the disease and the implications thereof. 10 It is reported that after the stabilization of the clinical picture and the care, being able to be at home, the patient was discharged from hospital, receiving instructions and plans of daily care.…”
Section: During Shiftmentioning
confidence: 99%
“…It is reported that, according to this model, it is the duty of the nurse to promote the adaptive responses of the individual to changes in physiological needs, selfconcept and interdependent relationships during health and illness. 12,14,19 It was observed that the repercussions of the spinal cord injury affect the individual, the family and society, so that their coping leads the family to organize to better understand the individual and to learn to live with the disease and the implications thereof. 10 It is reported that after the stabilization of the clinical picture and the care, being able to be at home, the patient was discharged from hospital, receiving instructions and plans of daily care.…”
Section: During Shiftmentioning
confidence: 99%